2008
DOI: 10.1007/s12185-008-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

A safety, pharmacokinetic and pharmacodynamic investigation of deferasirox (Exjade®, ICL670) in patients with transfusion-dependent anemias and iron-overload: a Phase I study in Japan

Abstract: The pharmacokinetics (PK) and pharmacodynamics (PD) of the once-daily, oral ironchelating agent, deferasirox (Exjade, ICL670), have been evaluated further in a Phase I, openlabel, multicenter, dose-escalation study in Japanese patients with myelodysplastic syndromes, aplastic anemia, and other anemias. Deferasirox was initially administered as a single dose of 5 (n = 6), 10 (n = 7), 20 (n = 6) or 30 (n = 7) mg/(kg day) and then after 7 days seven daily doses were administered. Linear PK (C (max) and AUC) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Thus far, there are limited data on largescale evaluation of iron chelation practice especially in terms of its clinical efficacy and safety profile in the Asian population [12]. To date, most studies were hampered by small sample sizes and the limited numbers of patients representative of the different ethnic origins found in this region [13][14][15][16] Deferasirox, a novel once-daily oral iron chelator, has been available for use in clinical practice since 2005 for the treatment of transfusional iron overload in adult and paediatric patients at least 2 years of age. The efficacy and safety of deferasirox in thalassaemia patients has been well-documented [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, there are limited data on largescale evaluation of iron chelation practice especially in terms of its clinical efficacy and safety profile in the Asian population [12]. To date, most studies were hampered by small sample sizes and the limited numbers of patients representative of the different ethnic origins found in this region [13][14][15][16] Deferasirox, a novel once-daily oral iron chelator, has been available for use in clinical practice since 2005 for the treatment of transfusional iron overload in adult and paediatric patients at least 2 years of age. The efficacy and safety of deferasirox in thalassaemia patients has been well-documented [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of deferasirox in thalassaemia patients has been well-documented [17][18][19][20]. However, most of the previous trials were conducted in thalassaemia patients outside the AP region and data on its use in the region is rather limited [16]. In addition, recent data from Thailand showed that local thalassaemia patients appeared to develop a significantly higher rate of mild cutaneous rashes with deferasirox exposure than what has been reported in the literature (18% Thai vs. 10-11% Caucasian patients) [17,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, Takatoku et al [1] reported that only 8.6% of Japanese patients with transfusion iron overload were treated with effective daily or continuous administration of deferoxamin, which must be applied as a continuous subcutaneous infusion and often results in poor compliance. Recently, the use of a novel once-daily oral chelator, deferasirox, was approved in Japan, and it is providing effective convenient therapy with safety and tolerability [2]. Herein, we report a case of a transfusiondependent MDS patient with iron overload, who was successfully treated with deferasirox, resulting in not only reduced iron level of serum ferritin, but also decrease in red blood cell (RBC) transfusion requirement and suspension of platelet (PC) transfusion.…”
mentioning
confidence: 99%
“…She had received intermittent intravenous deferoxamine (500 mg per week) from July 1996, but her serum ferritin level gradually increased. The patient was enrolled in a Phase I study of deferasirox in July 2005 [4]. At the time, serum ferritin was elevated to 17,000 ng/mL.…”
mentioning
confidence: 99%